Improving Motivation and Learning Outcomes With Contextual Teaching and Learning Strategies for Students in the Mathematics Education Study Program - Amelia, Puspa; Niniwati, Niniwati (Edumatica : Jurnal Pendidikan Matematika, 2019)
Abstract This research aims to improve the student’s learning achivements and motivation in learning analityc geometry of mathematic education’s students at Bung Hatta University by using Contextual Teaching and Learning (CTL) strategy. This was a classroom action research with the research study was 38 of class A of mathematic education’s students who took a course of analityc geometry. The data was collected from quisioner student’s, field notes and final test. The data analysis was conducted in descriptive qualitative through data reduction, triangulation, and data display. Based on the research’s result can conclude that learning process by using CTL strategy can improve motivation and learning outcome in Field Analityc Geometry Class. The questioner of student’s learningmotivation showed that there are improving from 54,97 % on the cycle to 66,31 % on the cycle.The student’s learning result also improved from 24,32 % on the cycle to 70,27 % on the cycle. Key Word :contextual teaching and learning (ctl), learning activities, learning motivation, learning result.